If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9m=-3m+2
We simplify the equation to the form, which is simple to understand
9m=-3m+2
We move all terms containing m to the left and all other terms to the right.
+9m+3m=+2
We simplify left and right side of the equation.
+12m=+2
We divide both sides of the equation by 12 to get m.
m=0.16666666666667
| 2d-3=-15 | | 4x-(3x+2)=(5x+3) | | X=3.30th | | 3+2x+1=4x | | 10x-35+3ax=5ax-7x | | 3(4x+2)=14 | | -16.8x=138.264 | | (25-5y)=4x-9y+13 | | 7(x+1)=4[x-3(3-x)] | | 5(x-12)= | | -6(1+2k)=-6-4k | | 2(4+20-1)= | | n+.6=n | | -3(2X-1)+5=50 | | 1+8n+5=-2 | | (3)(2)(-30)= | | 10x-3=5x+10 | | -14x+5y=19 | | 4(b-6)=71-2b | | 15+18-12=x | | 10p(1+9p)=8p^2 | | .667x+5=4 | | 8+20(3x+1)= | | 12x-8=8x-28 | | 2x-27-10=16 | | 4+x+3= | | x*5x=20 | | 2m+5=5m-7-5m | | -10x+2=10 | | 4x^2+10x=x+8 | | -10(-v+3)+6(v-11)=v+3+6 | | 54=4x^2-2X-2 |